Cover Feature: Bidentate Disilicate Framework for Bis‐Grafted Surface Species (Chem. Eur. J. 47/2021). Issue 47 (6th August 2021) - Ishizaka, Yusuke; Arai, Natsumi; Matsumoto, Kazuhiro; Nagashima, Hiroki; Takeuchi, Katsuhiko; Fukaya, Norihisa; Yasuda, Hiroyuki; Sato, Kazuhiko; Choi, Jun‐Chul
Abstract : Grafting of a platinum precursor bearing a disilicate ligand, −OSi(O t Bu)2 OSi(O t Bu)2 O−, achieved the selective formation of bis‐grafted surface species on silica supports. The chemical‐shift values of the ancillary ligands were almost identical before and after the grafting, thus suggesting that the coordination sphere around platinum of the grafted species was nearly independent of the type of silica support and the degree of substitution on the disilicate ligand. More information can be found in the Full Paper by J.‐C. Choi et al. (DOI: 10.1002/chem.202101927 ).